The Maturity Measurement of Big Data Adoption in Manufacturing Companies Using the TDWI Maturity Model - Fitri Retrialisca; Umi Chotijah (Universitas Airlangga, 2020)
Background: Big data technology has been used in several sectors in Indonesia. Adoption of big technology provides great potential for research, especially achievement in the implementation of big data in manufacturing companies. The Data Warehousing Institute (TDWI) Maturity Model is a tool that can be used to measure the state of